Antibacterial Bioactivity from Extract of Reundeu Caret (Staurogyne longata) and Honje (Etlingera hemisphaerica) - Noverita Noverita; Ernawati Sinaga (Universitas Nasional Jakarta, 2021)
Reundeu caret (Staurogyne longata) and Honje (Etlingera hemisphaerica) are two examples of plants commonly used by rural tribal communities as medicinal ingredients, one of which is by the Baduy tribal community. These two plans are usually used by local people to treat infectious diseases (wounds) and stomach aches. Therefore, it is necessary to prove the medical potential of these plants. This study was conducted with the aim of knowing the antibacterial potential of the extracts of the Reundeu caret (Staurogyne longata) and Honje (Etlingera hemisphaerica) plant extracts against the growth of Escherichia coli, Salmonella typhi, Staphylococcus aureus, and Bacillus cereus. The method used in this study is the Disc Diffusion method. The results showed that Reundeu caret and Honje plant extracts were only able to inhibit the growth of Staphylococcus aureus and Bacillus cereus. The antibacterial activity of the plant extracts of Rendeu Caret and Honje was moderate to strong. This study concluded that Honje and Reundeu caret plant extracts were more potential to be used to treat infectious diseases (wounds).